ASSOCIATION BETWEEN DIABETES MELLITUS AND OCULAR ANTERIOR SEGMENT MANIFESTATIONS IN COVID-19 PATIENTS - Ranita Ivana Cahyadi; Titiek Ernawati; Sindrawati (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: COVID-19 is an acute respiratory disease caused by the infection of SARS-CoV-2, which was also found to have ocular manifestations. In the previous study, SARS-CoV-2 was found in patients' conjunctival swabs and tear specimens. The SARS-CoV-2 binding sites were found on the conjunctiva and cornea of the eye. Diabetes mellitus is one of the most common comorbidities found in COVID-19 patients, at the same time, hyperglycemia in diabetes mellitus increases the risk of eye infections. This study aims to determine the association between diabetes mellitus and anterior segment ocular manifestations in COVID-19 patients.Methods: This research is an observational analytic cross-sectional study. Anterior segment ocular manifestations data were collected by patient-reported questionnaire due to high infection risk.Results: In the total of 169 COVID-19 patients in this study, 35 patients (20,7%) experienced anterior segment ocular manifestations, 50 patients (29,6%) had diabetes mellitus, and 12 patients (7,1%) experienced both. The most common ocular manifestations experienced were watery eyes (34,3%), red eyes (20,0%), and blurred vision (20,0%), as well as other complaints in the form of discharge from the eyes, itching, burning, foreign body sensation, pain, and glare at the light. While 12 of 50 diabetes mellitus patients (24%) had anterior segment ocular manifestations, 23 of 119 patients without diabetes mellitus (19.32%) experienced similar conditions. The results of data analysis with Chi-Square (p≥0.05) showed no significant association.Conclusions: There is no association between diabetes mellitus and anterior segment ocular manifestations in COVID-19 patients.